The determinants of corporate capital structure of Nigerian firms - Okonma, Patrick (2017)
This paper employs data of 71 non-financial firms listed on the Nigerian stock exchange from 2007 to 2016 with the objective of documenting their capital structure determinants. Debt, the dependent variable is divided into three categories: long term, short term and total debt to enable for a detailed analysis. Also, the panel data estimation methods are conducted to allow for a comprehensive study. The findings of the pooled OLS regression output indicates that five of the seven variables tested are significant in explaining leverage ratios. Tangibility has a positive relationship with long term and total debt ratio. This suggests that tangible fixed assets appear to be an important consideration for securing long term debts in Nigeria. Profitability is negatively significant with all debt ratios, confirming the pecking order theory. Size and growth are both positively related with all measures of leverage but dividends are negatively related. Earnings volatility and non-debt tax shield are found to be insignificant in explaining leverage ratios. The growth variable remains the only significant variable when the fixed effects model is performed. Also, the analysis of data in the study reveals that the majority of Nigerian firms are equity finance and that the structure of debt used were mainly short-term debts. Key words: Capital structure, leverage, panel data, Nigeria.